2016
DOI: 10.3109/02770903.2016.1171338
|View full text |Cite
|
Sign up to set email alerts
|

Cost of severe asthma in Brazil—systematic review

Abstract: Hospitalizations and medications seem to be the most important resources funded by the Brazilian public health system and by patients and their families. Although further studies are necessary, as information on cost of this disease is scarce in Brazil, these findings suggest that there is a potential room for improving severe asthma care among Brazilian patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
0
17
0
3
Order By: Relevance
“…A recent systematic review of the costs of severe asthma in Brazil showed that the major direct expenses were related to hospitalizations and medications and that USD 733.00 were spent per patient per year, highlighting the elevated economic costs of asthma. 32 …”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of the costs of severe asthma in Brazil showed that the major direct expenses were related to hospitalizations and medications and that USD 733.00 were spent per patient per year, highlighting the elevated economic costs of asthma. 32 …”
Section: Discussionmentioning
confidence: 99%
“…The authors emphasized that the indirect costs due to work productivity losses further increase the burden of disease. Other authors have analyzed the cost of severe asthma from the perspective of the Brazilian public health system 27 , describing a mean annual cost due to hospital admissions of 764-929 USD. The authors concluded that hospitalizations and drug treatments are the most important costs and underlined that further representative severe asthma cost studies in Brazilian patients are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies are published in Brazil with primary data on the costs of chronic diseases, and most of them refer to cardiovascular diseases, such as chronic coronary artery disease 20 and congestive heart failure 3 . A recent systematic review has included only three studies on the costs of asthma in Brazil, all focusing only on severe asthma, showing the scarcity of data in the country 25 . Our study provides an estimate of the cost of bronchial asthma in a real-life setting with outpatients with different levels of severity and control, not yet described in Brazil.…”
Section: Discussionmentioning
confidence: 99%